Cryosurgery as an Option for the Treatment of Vascular Lesions of the Oral Cavity - Pedro Thalles Bernardo de Carvalho Nogueira; Mariana Maria Castro Jatobá Remigio; Andreza Maria Correia de Queiroz; Andréia Aparecida da Silva; José Rodrigues Laureano Filho (Case Reports in Otolaryngology)
Cryosurgery is a treatment modality consisting in the destruction of tissue by the application of extremely low temperatures. This causes irreversible damage to cellular metabolism, leading to tissue destruction within minutes, a mechanism that may be beneficial when used in diseased tissues. Because cryosurgery is effective, simple, and easy to perform, it has been used in the treatment of lesions in both medical and dental fields. This technique provides many advantages, such as easy operation, absence of intraoperative bleeding, and low infection rate. We report the case of a patient with a hemangiomatous lesion of the oral cavity who was treated with liquid nitrogen spray cryosurgery, with successful results at 18-month follow-up.